Pengaruh Book Tax Differences Dan Tingkat Hutang Terhadap Persistensi Laba Pada Perusahaan Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 - 2023 - Rahma Warnika, Widia; Sri Utami, Endang (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
In the decision-making process, information about profits plays an important role. The right decision often depends on the quality of the earnings information itself. Quality profits are profits that can provide an accurate indication of future porfit estimates. Consistency in earnings indicates superior earnings quality over time. In addition, differences between recorded profits in books and profits subject to tax (book tax differences) can affect profit persistance due to differences in the recognitions of incopme and costs according to accounting standards and tax regulations. Apart from that, another factor that also has the potential to influence profit persistence is the company’s debt level. In an effort to explore the impact of book tax differences, as well as debt levels on earnings persistence, this research was conducted with a clear aim. The method in used is a careful quantitative approach. The population studied included companies in the banking sector listed on the Indonesia Stock Exchange (BEI) during the period 2019 to 2023. The sample selection procedure was carried out using SPSS 26 software to analyze the patterns that emerged. From the results of the analysis that has been carried out, it was found that there is a significant and positive influence between the difference between profit recognition in financial statements and tax imposition on the resilience of company profits. On the other hand, ther is no significant relationship between the level of company debt and earnings resilience measured in this research.